2020
DOI: 10.1007/s12070-020-02114-2
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Total Thyroidectomy in Painful (Symptomatic) Hashimoto’s Thyroiditis: Descriptive Study

Abstract: Hakura Hashimoto described Hashimoto’s Thyroiditis (HT) in 1912. In HT, there occurs formation of antibodies against the self (thyroid), which causes enlargement of the thyroid gland as a whole and decreased thyroid hormone levels. Most of the patients with HT are given medical line of management (hypo/hyperthyroidism). The indications for surgical line of management for HT are due to pressure symptoms over the trachea and oesophagus, pain in the thyroid gland and for chance of malignancy. Surgical treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…All these studies have shown that patients with thyroiditis had significantly improved preoperative symptoms after thyroidectomy and benefitted regarding QoL. With more elaboration, there was a complete improvement in compressive and painful symptoms [7]. Most symptomatic HT patients had relief of their symptoms after surgery [12].…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…All these studies have shown that patients with thyroiditis had significantly improved preoperative symptoms after thyroidectomy and benefitted regarding QoL. With more elaboration, there was a complete improvement in compressive and painful symptoms [7]. Most symptomatic HT patients had relief of their symptoms after surgery [12].…”
Section: Resultsmentioning
confidence: 98%
“…The locations of the publishing authors demonstrated good variation, including the United States, Europe, Asia, and Australia. Of these studies, 10 were designed as retrospective reviews [4][5][6][9][10][11][12][13][14]17], four as prospective studies [7,15,16,19], and two as systematic reviews [8,18]. The sample size ranged from 10 to 18,955 patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations